Trade linkages and macroeconomic effects of the price of oil - Iikka Korhonen; Svetlana Ledyaeva (Bank of Finland, Institute for Economies in Transition (BOFIT), 2008)
In this paper we assess the impact of oil price shocks on oil-producer and oil-consumer economies. VAR models for different countries are linked together via a trade matrix, as in Abeysinghe (2001). As expected, we find that oil producers (Russia and Canada here) benefit from oil price shocks. For example, a large oil shock, leading to a price increase of 50%, boosts Russian GDP by some 12%. However, oil producers are hurt by indirect effects of oil shocks, as economic activity in their export countries suffers. For oil consumers, the effects are more diverse. In some countries, output drops in response to an oil price shock, while other countries seem to be relatively immune to oil price changes. Finally, indirect effects are also detected for oil-consumer countries. Those countries trading more with oil producers receive indirect benefits via higher demand from the oil producing countries. In general the largest negative total effects from positive oil price shocks are found in China, USA and Japan while European countries seem to fare quite well during recent positive oil-price shocks.
URN:NBN:fi:bof-201408072210
Keywords: 330